Differences in Pain Intensity of Tumors Spread to the Anterior versus Anterolateral/Lateral Portions of the Vertebral Body Based on CT Scans - Hui-Ching Hsu; Tzu-Yao Liao; Long-Sun Ro; Yu-Hsiang Juan; Chuang-Chi Liaw (Pain Research and Management)
We investigated whether the intensity of cancer pain differs for malignant tumors that have spread to anterior or anterolateral/lateral portions of the vertebral body. We hypothesize that tumor spread to the anterolateral/lateral vertebral body elicits more serious pain due to increased irritation of the spinal nerve. The selection criteria were as follows: (1) advanced or metastatic solid tumor; (2) radicular pain without extremity weakness; (3) malignant lesions anteriorly, anterolaterally, or laterally located at the vertebral body either spread locoregionally or over a greater distance via metastasis based on CT scan diagnosis; and (4) patient needs to use opioids for pain relief. Severe spinal pain intensity was defined as spinal pain for which patients required either strong opioids or spinal irradiation for relief. Eighty-six patients were enrolled in the study. Bone lesions were mainly osteolytic. Thirty-nine tumors spread to the vertebral body in the anterior direction, and 47 in the anterolateral/lateral direction. Severe pain intensity related to vertebral body lesions was due to anterolateral/lateral spread, primary sites of nonurothelial carcinoma, metastatic vertebral lesions, multiple lesions within a vertebrum, and location within the cervical-thoracic spine. In conclusion, patients with tumor spread to the anterolateral/lateral portion of vertebrae bodies based on CT scan diagnosis experienced severe cancer pain. These patients needed strong opioids or palliative spinal irradiation for pain relief.